The Influence of Giving Reward And Punishment on Student Learning Motivation - Medy Dwi Indardi (Universitas Negeri Semarang, 2023)
Motivation something Power mover in self-somebody in form activity real For do something goals, motivation study is very necessary in learning less students own motivation Study can impact bad at the learning process . Motivation determine succeed or the failure activity Study student , with reward and punishment for student can expected increase motivation Study student . Giving reward and punishment to students can guide student active , and can create a more optimal learning process . Less student own motivation Study can become must problem solved. Study This aim for analyze is reward can give influence increasing motivation Study student. Method : Study This use approach literature review was carried out based on study from various journals , proposals, books . Results: Based on study a number of reward and punishment literature has an effect on improvement motivation Study student.